Don’t be Too Strict with Yourself! Rigid Negative Self-Representation in Healthy Subjects Mimics the Neurocognitive Profile of Depression for Autobiographical Memory - Sperduti, Marco; Martinelli, Pénélope; Kalenzaga, Sandrine; Devauchelle, Anne-Dominique; Lion, Stéphanie; Malherbe, Caroline; Gallarda, Thierry; Amado, Isabelle; Krebs, Marie-Odile; Oppenheim, Catherine; Piolino, Pascale (Frontiers in Behavioral Neuroscience, 2013)
Autobiographical memory (AM) comprises representation of specific (episodic) and generic personal information (semantic). Depression is characterized by a shift from episodic to semantic AM retrieval (“overgeneralization”). Theoretical models have proposed that this effect could be linked to reduced executive resources. Moreover, “overgeneral” memories, accompanied by a negativity bias in depression, lead to a pervasive negative self-representation. Even in “non clinical” populations executive functions and AM specificity are closely linked, and “overgeneral” memories could result in depressive emotional responses. We made the hypothesis that healthy subjects showing a rigid negative self-image would mimic the neurocognitive profile of patients. We measured executive functions and the self-image in young healthy subjects, and recorded their brain activity, by means of fMRI, while they retrieved episodic AMs. We report that a more rigid negative self-image corresponds to lower executive functions and less vivid specific memories. Moreover, higher negative self-image is accompanied by attenuated activity in the left ventrolateral prefrontal and in the anterior cingulate cortex, that have been repeatedly shown to exhibit altered functionality in depression. Activity in these regions, on the contrary, positively correlates with executive and memories performances, in agreement with their role in executive functions and AM retrieval. We claim that rigid negative self-image could represent a marker or a vulnerability trait of depression that is linked to reduced executive functions efficiency and to episodic AM decline. Our results are encouraging for psychotherapeutic approaches promoting cognitive flexibility in depression and other psychiatric disorders.